2020
DOI: 10.14507/epaa.28.5012
|View full text |Cite
|
Sign up to set email alerts
|

Using global observation protocols to inform research on teaching effectiveness and school improvement: Strengths and emerging limitations

Abstract: An essential feature of many modern teacher observation protocols is their “global” approach to measuring instruction. Global protocols provide a summary evaluation of multiple domains of instruction from observers’ overall review of classroom processes.  Although these protocols have demonstrated strengths, including their comprehensiveness and advanced state of development, in this analysis we argue that global protocols also have inherent limitations affecting both research use and applied school improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
0
20
0
4
Order By: Relevance
“…This effectively limits the range of teacher intentions and learning goals that will be encountered when using IQA, which in principle allows the IQA to be more carefully tailored to those teacher intentions. If one takes a strong view about the importance of teacher intentions, measuring teaching quality accurately may require using specialized systems that narrowly capture only key aspects of teaching quality (Kelly et al, 2020).…”
Section: Assumption 1: Teaching Is An Intentional Activitymentioning
confidence: 99%
“…This effectively limits the range of teacher intentions and learning goals that will be encountered when using IQA, which in principle allows the IQA to be more carefully tailored to those teacher intentions. If one takes a strong view about the importance of teacher intentions, measuring teaching quality accurately may require using specialized systems that narrowly capture only key aspects of teaching quality (Kelly et al, 2020).…”
Section: Assumption 1: Teaching Is An Intentional Activitymentioning
confidence: 99%
“…To that end, we believe that equity analytics and the development of tools to capture the distribution of opportunities to learn such as EQUIP (https://www.equip.ninja) offer some promise for answering the questions we mentioned above using equity ratios and have been used to examine how teachers might use such data to address implicit bias (Reinholz et al, 2020). Furthermore, such measures may be positioned well to measure teacher adaptation and change (Kelly et al, 2020). However, fine-grained observation instruments, including dyadic observation instruments, are often expensive and difficult to collect and implement (Kelly et al, 2020).…”
Section: Technology Toolsmentioning
confidence: 99%
“…Furthermore, such measures may be positioned well to measure teacher adaptation and change (Kelly et al, 2020). However, fine-grained observation instruments, including dyadic observation instruments, are often expensive and difficult to collect and implement (Kelly et al, 2020). For those reasons, we imagine that numerous tools and applications can be developed to measure and provide feedback on who participates in classrooms and the nature of that participation.…”
Section: Technology Toolsmentioning
confidence: 99%
“…Rating quality was further enhanced with calibration videos at the beginning of each rating session, by interspersing "validity videos" into each rater's workload, and by consultation with scoring leaders who "back-scored" a sub-sample of videos to identify raters who needed additional training. Despite generally adequate training and quality control for large-scale research purposes, several measurement limitations have been identified in the MET study, including imprecise discrimination in lesson quality, lack of independence in sub-domains, and sensitivity to rater training (see Kelly et al, 2020, for full discussion of limitations). Yet, at the present time we would still consider the six measures we use to be state-of-the-art measures of instruction.…”
Section: Observation and Instructional Measurement Processmentioning
confidence: 99%
“…The protocols used in MET are "global" protocols (Kelly et al, 2020), applying overall scores to multiple domains of practice from viewing segments of instruction. For example, CLASS is divided into three broad domains, emotional support, classroom organization, and instructional support, with those in turn made up of more specific subdomains (e.g., quality of feedback).…”
Section: Nature Of the Observational Measuresmentioning
confidence: 99%